The State as a Clearing House: Interest Organizations, the Common Good, and the Arduous Rise of Pluralist Democracy in Postwar Germany - Pankakoski, Timo (SAGE Publications, 2026)
This article retells the German intellectual history of political pluralism from a novel perspective: that of the state as a clearing house. In regular business transactions, clearing houses settle debts and mediate between buyers and sellers, bearing risks on both parties’ behalf for a fee. In politics, the clearing house image describes political pluralism, interest groups, and the common good metaphorically—and, in Germany, pejoratively at first. The clearing house topos emerged in Carl Schmitt’s interwar criticism of pluralism, parliamentarianism, and the League of Nations. Alongside Otto Kirchheimer, particularly the post-1945 Schmittian antipluralists Werner Weber and Winfried Martini adopted the term to criticize the “occupation” of the state by private interests. However, the clearing house metaphor was also reappropriated by defenders of the republic like Dolf Sternberger, Ernst Friesenhahn, Horst Ehmke, Günter Dürig, Ernst Fraenkel, and Otto Stammer. In their creative reinterpretations, the state as a mediator between rival interests and viewpoints became a moderately positive image—one not only compatible with the common good but, in fact, serving it. The analysis reminds us that the economic framing of pluralistic interests by no means automatically excludes considerations of the common good. Correspondingly, “clearing house” gradually turned from a word of abuse into an affirmative metaphor with prodemocratic pluralistic implications, thus capturing, in a microcosmic fashion, much of Germany’s postwar democratization. This was a collective process, and the discursive continuities with prewar antipluralism highlight how pluralist democracy lives off the linguistic resources at its disposal, occasionally by creative reinterpretation